2024
DOI: 10.1021/acs.analchem.3c05539
|View full text |Cite
|
Sign up to set email alerts
|

Comprehensive Impurity Profiling of mRNA: Evaluating Current Technologies and Advanced Analytical Techniques

Julien Camperi,
Steffen Lippold,
Luladey Ayalew
et al.

Abstract: In vitro transcription (IVT) of mRNA is a versatile platform for a broad range of biotechnological applications. Its rapid, scalable, and cost-effective production makes it a compelling choice for the development of mRNA-based cancer therapies and vaccines against infectious diseases. The impurities generated during mRNA production can potentially impact the safety and efficacy of mRNA therapeutics, but their structural complexity has not been investigated in detail yet. This study pioneers a comprehensive pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(5 citation statements)
references
References 42 publications
0
5
0
Order By: Relevance
“…Camperi et al performed a comparison of CGE, mCE, and SEC for the evaluation of covalent and non-covalent aggregates of mRNA under native and denatured conditions. Their results, obtained with a commercial ultra-wide pore SEC column packed with 1000 Å particles, confirm the possible application of SEC to assess aggregation of three different mRNA samples (i.e., eGFP, Fluc, and beta gal mRNA) from two different suppliers [ 13 ]. More recently, De Vos et al investigated the capabilities and limitations of SEC for the characterization of IVT mRNA samples of different sizes [ 18 ].…”
Section: Introductionmentioning
confidence: 71%
See 1 more Smart Citation
“…Camperi et al performed a comparison of CGE, mCE, and SEC for the evaluation of covalent and non-covalent aggregates of mRNA under native and denatured conditions. Their results, obtained with a commercial ultra-wide pore SEC column packed with 1000 Å particles, confirm the possible application of SEC to assess aggregation of three different mRNA samples (i.e., eGFP, Fluc, and beta gal mRNA) from two different suppliers [ 13 ]. More recently, De Vos et al investigated the capabilities and limitations of SEC for the characterization of IVT mRNA samples of different sizes [ 18 ].…”
Section: Introductionmentioning
confidence: 71%
“…However, capillary electrophoresis (CE)-based RNA integrity assays require relatively long run times and can sometimes show relatively high quantitation variability [ 8 ]. Microchip capillary electrophoresis (mCE) has recently been proposed as a quicker alternative for RNA samples consisting of up to 6000 nt [ 12 , 13 ]. Alternatively, ion-pairing reversed-phase liquid chromatography (IP-RPLC) has been widely used for the analysis of small oligonucleotides (ONs), but its application to larger ONs such as mRNA drugs is much more limited.…”
Section: Introductionmentioning
confidence: 99%
“…In the current report, we demonstrated that selective enzymatic digestion of RNA fragments (lacking a poly(A) tail), using minimal resources and no excessive heating, results in an unambiguous readout: any signal higher than the background luminescence is due to the presence of untailed mRNA fragments, which are all unwanted byproducts. However, byproducts such as 3' loop-back dsRNA and transcripts with shorter poly(A) tails are unlikely to be detected by the PNPase assay [ 9 , 17 ]. It is also important to note that the PNPase assay requires incubation at 37°C and hence also introduces some intra-assay cleavage events.…”
Section: Discussionmentioning
confidence: 99%
“…Fragmented mRNA is another common impurity that must be taken into account [ 26 , 27 ]. Only full-length mRNA transcripts containing both a 5′-cap and a 3′-poly(A) structure are viable for in vivo expression.…”
Section: Introductionmentioning
confidence: 99%